A Guide for the Optimum Selection of a Free Open Source Integrated Library System - Rousidis, Dimitris; Christodoulou, George (Qualitative and Quantitative Methods in Libraries; Vol 7 No 1 (2018): March 2018 Issue, 2019)
Many major studies have concluded that over the past years, Free Open Source Software (FOSS) projects have been growing exponentially. At the same time, a considerable number of companies, government organisations and libraries are taking advantage of the many merits of FOSS. The number of libraries that adopt open source tools, and more importantly migrate from their commercial system to a free open source Integrated Library System (ILS) keeps on increasing. In this paper, we performed a quantitative and qualitative analysis by examining the literature concerned with the use of FOS ILS in libraries, in order to identify the specifics, the characteristics, the utilities of these systems and we provide a walkthrough guide that will aid librarians to make the optimum selection for a FOS ILS.